A Unique Presentation of Anti-RNA Polymerase III Positive Systemic Sclerosis Sine Scleroderma. (31st July 2016) - Lee, Cody M.; Girnita, Diana; Sharma, Arundhati; Khanna, Surabhi; Elwing, Jean M.
Abstract : Systemic sclerosis is a rare autoimmune disorder with a wide spectrum of clinical manifestations and a multitude of autoantibodies that are associated with it. In the past several years, advances in serologic testing have led to research indicating important prognostic and phenotypic associations with certain subsets of autoantibodies. In particular, anti-RNA polymerase III (anti-RNAP III) has been associated with diffuse cutaneous disease, scleroderma renal crisis, a temporal relationship with malignancy, myositis, synovitis, joint contractures, and gastric antral vascular ectasia. However, anti-RNAP III has not been associated with systemic sclerosis sine scleroderma. We describe a patient with an atypical presentation of anti-RNAP III positive systemic sclerosis sine scleroderma who presented without the typical features of anti-RNAP III disease. Instead, she presented with critical digital ischemia, pulmonary arterial hypertension, gastroesophageal reflux disease, interstitial lung disease, and no clinically detectable sclerodactyly.